The Effect of Trust Dimension to E-Commerce Costumers Participation (Case Study to E-Commerce Costumers in Bima City) - Ismunandar Ismunandar; Mulyadin Mulyadin (JURNAL TERAPAN MANAJEMEN DAN BISNIS, 2018)
Transactions through e-commerce have a high potential risk. Therefore, the trust factor of customers towards the vendor becomes a key factor in e-commerce. Indonesia as a developing country and about the last five years adopted e-commerce, absolutely, has some differences with developed countries that have been long practicing it. These differences are at least related to regulatory issues, legal device, and consumer behavior. In relation to the e-commerce practice in Bima city that is still relatively new, the interesting phenomenon to be studied is the extent to which customers trust and how it affects the level of customer participation in e-commerce. The aims of this research are (1) to analyze the effect of the trust dimension variable which includes ability, virtue, and integrity to Indonesian costumers participation; (2) As information about the trust dimension of costumers e-commerce in Bima city, so the company can choose the right strategy to improve trust and people participation in using e-commerce as a future business transaction system. The study has been conducting in Bima city for 1 year from December 2017 to December 2018. This research is divided into several steps, namely 1) Preparation (2) Implementation, (3) Reporting, (4) Monitoring, evaluation, and dissemination. The technique of data collection used in this study that is (1) Questionnaire, (2) Observation, (3) Study book. Technique of Data Collection used is multiple regression analysis using equation, that is: Y = a + b1x1 + b2x2 + b3x3. The results of the study concluded that the dimensions of trust, ability, and benevolence have a positive and significant effect on the participation of e-commerce customers in Bima City. While variable integrity does not have a positive and significant effect. Meanwhile, testing these three variables together has a positive and significant influence.